2021
DOI: 10.1155/2021/8127145
|View full text |Cite
|
Sign up to set email alerts
|

Hub Gene and Its Key Effects on Diffuse Large B-Cell Lymphoma by Weighted Gene Coexpression Network Analysis

Abstract: Diffuse large B-cell lymphoma (DLBC) is a kind of tumor with rapid progress and poor prognosis. Therefore, it is necessary to explore new biomarkers or therapeutic targets to assist in diagnosis or treatment. This study is aimed at screening hub genes by weighted gene coexpression network analysis (WGCNA) and exploring the significance of overall survival (OS) in DLBC patients. Statistical data using WGCNA to analyze mRNA expression in DLBC patients came from The Cancer Genome Atlas (TCGA) dataset. After analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The expression level of TMEM176B was higher in gastric cancer tissues than in normal tissues, and according to survival analysis, higher expression levels were related to poorer prognosis ( Sun et al, 2018 ). The expression of TMEM176B in lymphoma and its control tissues also differed significantly ( Cuajungco et al, 2012 ; Ma and Li, 2021 ). The expression of TMEM176B is up-regulated in the tumor blood vessels of human renal cell carcinoma specimens, suggesting that it is implicated in tumor angiogenesis and could be a target of anti-angiogenesis therapy for cancer patients ( Otsubo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of TMEM176B was higher in gastric cancer tissues than in normal tissues, and according to survival analysis, higher expression levels were related to poorer prognosis ( Sun et al, 2018 ). The expression of TMEM176B in lymphoma and its control tissues also differed significantly ( Cuajungco et al, 2012 ; Ma and Li, 2021 ). The expression of TMEM176B is up-regulated in the tumor blood vessels of human renal cell carcinoma specimens, suggesting that it is implicated in tumor angiogenesis and could be a target of anti-angiogenesis therapy for cancer patients ( Otsubo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WGCNA implements methods for both weighted and unweighted correlation networks and provides a more effective mean to explore the hub genes that regulate critical biological processes ( Barabási et al, 2011 ). To date, WGCNA has been successfully applied for identifying potential biomarkers with diagnostic and prognostic values in a wide range of cancer types ( Liu et al, 2021 ; Ma and Li, 2021 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has suggested that IGFBP4 is associated with poor outcomes in glioblastoma ( 42 ). Interestingly, in diffuse large B cell lymphoma (DLBCL) patients, the C1qA [276] polymorphism of the A/A allele is an independent favorable prognostic factor for rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) as first-line therapy ( 43 ), while the expression level of LGALS2 was not associated with OS but was lower in tumors than in normal samples ( 44 ). LAMP3 is over-expressed in various tumors and is correlated with the poor or good prognosis of different patients ( 45 ).…”
Section: Discussionmentioning
confidence: 99%